A estabilização da tutela antecipada antecedente no novo CPC - Silva, Erivando Joter da (2015)
The stabilization of satisfativa previous preliminary injunction is an institute that was positivado recently in the parental rights with the advent of the New Code of Civil Procedure (NCPC), which comes down to the maintenance of the effects of a favorable interim provision the applicant, which was not contested by the defendant within the statutory period for challenging the summary judgment. As a result, the present study has the general objective of analyzing the nature and function of stabilizing the foregoing satisfativa guardianship, observing the general regramento and the nuances and possible outlines that the institute will take because of his assertiveness in the new code, as concerns the protection of procedural effectiveness the right to distribute equally the burden of time, when present the assumptions of the prima facie juris and periculum in arrears, as well as for the autonomy of decision granting the interim appointment. It is a survey that will use as study material bibliographic sources that record the current debate about the object of research, aiming at an approach according to the qualitative nature of our survey, including use of works of national authors who comment on legislation and foreign doctrine, so that there incursion study the comparative law. In addition to the doctrinal approach to the issue, also will carry out research case law where necessary, aiming a better basis for the scientific enterprise by analyzing and comparing the results of bibliographic research to forensic reality in order to combine theory and practice. After observing the object of study, it is identified that the the stabilization of the previous preliminary injunction undergoes regramento of interim protection, which provides for emergency protection and evidence, as well as to the general regramento of emergency guardianship, whose species are tutelage interim and injunctive relief. Moreover, it was found that the Brazilian legislator came under the influence of French law and Italian, that there have been attempts to include the stabilization of guardianship in the presence of CPC / 73, that the NCPC has designated a specific procedure for granting the preliminary injunction aimed at stabilizing If and granted the provisional measure, it will stabilize only if the defendant remains inert and can either party within two years stabilized challenge the decision by an autonomous action. Also, it found out that the majority doctrine holds that the stabilized decision makes res judicata, by the legislature itself option, even after two years of stabilization of the decision and can not be handled a rescission action. Finally, it analyzed it is appropriate to apply the institute in actions against the tax authorities and there is no obstacle in law. Based on the foregoing, we conclude that the Brazilian legislator treated differently institute at some points the way it was designed and implemented in comparative law. In addition, the legislator tried to incompletely the institute, leaving several controversial points, which constitute ground for doctrinal discussion, but that need to be bypassed by the own legislature and the judiciary on the grounds of legal certainty.